Affixation of Taro Dialect: A Descriptive Study - Artawan, Kadek (Language and Education Journal Undiksha, 2018)
This descriptive study aimed at describing the number of prefixes and suffixes in Taro Dialect and its types of inflectional and derivational. This study is a descriptive qualitative research. Two informant samples of Taro Dialect were chosen based on a set of criteria. The data were collected based on three techniques, namely; observation, recording technique, and interview (listening and noting) technique. The results of the study show that there were five prefixes and five suffixes existing in Taro Dialect. The prefixes were N-, {ma-}, {sa-}, {pa-}, and {ka-}. The suffixes were {-in}, {-ne}, {-an}, {-ang}, and {-e}. The prefixes and suffixes that belong to derivation are: prefix N-, {ma-}, {sa-}, {pa}, and {ka-} and suffix {-ang}, {an}, {-ne}, and {-in}. The prefixes and suffixes that belong to inflection are: prefixes N-, {ma-}, and {ka-} and suffix {-ang}, {an}, {-ne}, {-in}, and {-e}.